Experimental investigation of buoy frame width on water motorbike stability response time - Irwansyah; Weriono; Ibnu Hajar; Burhan Hafid; M. Muttaqin; Ari Purnomo (JTTM : Jurnal Terapan Teknik Mesin, 2025)
This study investigates the impact of buoy frame width on the stability response time of water motorbikes, focusing on their ability to regain equilibrium after tilting. Water motorbikes are innovative vehicles designed to navigate flood-prone areas where conventional motorcycles cannot operate effectively. To enhance stability, buoyant frames of varying widths—40 cm, 45 cm, and 50 cm—were tested at three initial tilt angles: 5°, 10°, and 15°. The research employed an experimental approach, utilizing digital inclinometers to measure tilt angles and stopwatches to record response times. Data analysis revealed that frame width significantly affects stability, with wider frames yielding faster response times. For instance, at a 5° tilt angle, the 50 cm frame achieved a response time of 3.12 seconds, compared to 4.84 seconds for the 40 cm frame. Similarly, wider frames consistently outperformed narrower configurations across all tested angles. ANOVA results confirmed the statistical significance of the findings, with p-values less than 0.05. The results demonstrate that increasing the width of buoy frames enhances the stability of water motorbikes, making them more efficient and reliable for use in flood-affected areas. These findings provide valuable insights into the design and optimization of water motorbikes, contributing to safer and more practical solutions for flood navigation.